An Exploratory Study of Sustaining Organisational Agility - Senapathi, M; Strode, DE (Elsevier BV, 2025)
Context: How an organisation sustains agility over time, and the actions it takes when encountering challenges to its agility, are not well established. Objective: This study explores how an organisation sustained its agility beyond the initial adoption stage when its agility was founded on the values, principles, and practices of agile software development. Method: A qualitative case study of the Retail organisation within a company was carried out. The Retail organisation had sustained agility for six years. Results: Nine main challenges are: disparate levels of maturity, resistance to change, competing priorities, lack of team empowerment, dependencies between teams, onboarding people to the agile way of working, lack of role clarity, staff turnover, and incompatible funding model. Based on the solutions to these challenges, eight general actions applied to sustain agility are: a clear reason for implementing agile principles, continuously raising agile awareness, continuously adjusting the business operating model, embedding specialist agile roles, changing the funding model, making work visible, supporting agile teamwork, and monitor, measure, feedback, and act. Conclusions: The contributions of this article are practical. The challenges, detailed solutions, and general actions identified could be helpful for organisations that need to sustain agility in contexts similar to the case organisation. The findings should enable synthesis with future case studies and potential theory-building.
Keywords: 46 Information and Computing Sciences; 4609 Information Systems; 4612 Software Engineering; 8.1 Organisation and delivery of services; 0803 Computer Software; 0806 Information Systems; Software Engineering; 4612 Software engineering